An analysis of the efficacy of uterine artery embolization in obstetrical hemorrhage - Srivastava, Ritika; Mehta, P. K.; Indusekhar (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: Obstetrical hemorrhage is the single most important cause of maternal morbidity and mortality. The study is conducted at a tertiary-care hospital to assess the efficacy of uterine artery embolization as a treatment for obstetrical uterine hemorrhage. It examines various aspects such as the outcome of the procedure, need of blood and blood products, need of secondary procedures post intervention and the possibility of future pregnancies. Methods: It was a retrospective observational study conducted with sample size of 20 patients with obstetrical hemorrhage at the Department of Obstetrics and Gynecology of Bhagwan Mahaveer Jain Hospital, Bengaluru in India between January 2011 to July 2019. Results: Records of 20 patients with obstetrical hemorrhage were assessed. The study indicates that 11 patients experienced postpartum hemorrhage (PPH), 5 postabortal bleeding & 4 bleeding due to scar ectopic. Out of 20 patients, hemodynamic stability was achieved in 17 cases (85%), hysterectomy was needed in 2 cases (10%) and 1 (5%) patient died after the procedure. Of total 20 cases, 18 (90%) required secondary procedures post-intervention like dilatation and evacuation 6 cases (33.3% of total cases), vaginal suturing and packing 10 cases (55.5% of total cases) and supportive measures like PPH and Disseminated intravascular coagulation (DIC) management in 2 cases (11.1% of total cases). Blood transfusion was given in 15 cases (75%) after the procedure. Future pregnancy was attained in 8 cases (47%) after considering the history of the patients, loss of follow-up, possibility of complications, family planning and hysterectomy performed. Conclusions: Uterine artery embolization is a very effective method to control obstetric hemorrhage with high success and low complication rate and hysterectomy can be avoided to preserve fertility.